India's Africa policy - Wagner, Christian (2019)
Zusammenfassung: Since the 1990s, India has significantly widened its relations with Africa. Three summits, increasing trade and newly agreed cooperation on security demonstrate the increased importance of the African continent to India's foreign policy. With this commitment to Africa, India continually underscores its claim to act as advocate for the countries of the Global South. Moreover, African countries now account for a larger share of India's energy imports, thereby reducing its dependence on Middle Eastern countries. India is also trying to establish a counterweight to China’s activities in Africa. However, India’s decision-makers realise that they cannot seriously compete with China in this arena. Germany and India share a number of similar economic and political interests. There is therefore great potential for closer cooperation in Africa and the Indian Ocean. The common goal is to strengthen state institutions in Africa, to promote economic development, and to prevent African states from becoming unilaterally dependent on third countries, especially China. This could potentially be translated into a number of programmes as part of triangular cooperation between India, Germany and African countries, such as capacity building, initial and further training, and the strengthening of small and medium-sized enterprises. Particularly in the context of the strategic partnership between India and Germany, this could be an important step in taking bilateral relations to a new level